If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 3 = 73 Reorder the terms: 3 + 26x = 73 Solving 3 + 26x = 73 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 26x = 73 + -3 Combine like terms: 3 + -3 = 0 0 + 26x = 73 + -3 26x = 73 + -3 Combine like terms: 73 + -3 = 70 26x = 70 Divide each side by '26'. x = 2.692307692 Simplifying x = 2.692307692
| X^2+9+100=676 | | z-3/4z | | -220+.25q=2120-.05q | | 4/(5-8i) | | 3/4c=-9 | | 15+49=2.2b+b | | 6c+1+54=59 | | 3x^4+34x^2+63=0 | | 2x+4=8-5x | | 38/20= | | -9+n=18 | | 2x+=8-5x | | 7r+1*5=10 | | X^2+9+10=676 | | f(0)=3(0)-9 | | -220+.025q=2120-.05q | | 2/3x-4=18-1/4x | | 2/3*6x=33 | | (2x-9)+(X+8)=180 | | 1/5/6-3/3/8= | | 5.2x+3.8=14.2 | | x(y/y-x)^2= | | (4-3i)(2-i)(3i)=0 | | 7xy+y^2= | | 150000=-20x^2+5000x | | p=-220+.25q | | w/3-3.3=-10.8 | | 7=1.2x+3 | | 5x^2-14.7x=0 | | 2/3(6x)=33 | | 5x-2(6x+11)=55 | | 9y=6y+21 |